Effect of exercise on metabolic syndrome in black women by family history and predicted risk of breast cancer: The FIERCE Study. Issue 16 (5th July 2018) - Dash, Chiranjeev; Taylor, Teletia R.; Makambi, Kepher H.; Hicks, Jennifer; Hagberg, James M.; Adams‐Campbell, Lucile L.
Abstract : Background: This study examined the effects of supervised and home‐based exercise interventions on changes in metabolic syndrome (MetS) according to breast cancer risk (high vs low) in black women enrolled in the Focused Intervention on Exercise to Reduce Cancer (FIERCE) trial. Methods: Postmenopausal, obese, metabolically unhealthy black women, 45 to 65 years old, were randomized to supervised aerobic exercise (73 women), home‐based walking‐based exercise (69 women), or a control arm (71 women). Participants in the exercise arms underwent a 6‐month intervention with study assessments conducted at the baseline and 6 months. The primary outcome measure was MetS (fasting glucose, waist circumference, blood pressure, serum triglycerides, and high‐density lipoprotein [HDL]). The intervention effects on MetS, stratified by breast cancer risk as measured by the family history of breast cancer and model‐based projected breast cancer risk, were examined with intent‐to‐treat analyses using generalized estimating equation models. Results: Among women with a family history of breast cancer, the exercise arms had lower mean MetS z scores, which suggested an improvement in the metabolic profile, than controls at 6 months (controls, + 0.55; home‐based arm, –0.97, P < .01; supervised arm, –0.89, P < .01). Stratified analyses by projected breast cancer risk suggested similar but statistically nonsignificant findings, with those at high risk having more favorable changes in the MetS z score in the exercise arms versus the control arm. These changes were primarily attributable to changes in blood pressure, triglycerides, and HDL. Conclusions: Short‐term aerobic activity regimens may improve the metabolic profile and thereby reduce breast cancer risk in obese, metabolically unhealthy black women at high risk for cancer. © 2018 American Cancer Society . Abstract : This randomized controlled trial examines the effects of supervised and home‐based exercise interventions on changes in metabolic syndrome according to the breast cancer risk (high vs low) in black women enrolled in the Focused Intervention on Exercise to Reduce Cancer (FIERCE) study. The results suggest that short‐term aerobic activity regimens may improve the metabolic profile and thereby reduce the breast cancer risk in obese, metabolically unhealthy black women at high risk for cancer.